Biodiesel production from waste cooking oil : A brief review - Suzihaque, M. U.H.; Habsah, Alwi; Ummi Kalthum, Ibrahim; Sureena, Abdullah; Normah, Haron (Elsevier Ltd, 2022)
Biodiesel is a source of new renewable energies and a substitute fuel with much potential in the future for petroleum-derived diesel. According to BP Statistical Review of World Energy, total global consumption of diesel from petroleum increasing in one decade which is 3.5 million tonnes in 2010 and 3.9 million tonnes in 2019. Despite reducing the dependence on fossil fuel, the question of how waste cooking oil (WCO) disposal and related environmental damage issues might be solved by biodiesel production. In Malaysia, an estimated 540 000 tonnes of WCO from vegetable and animal fats are discarded each year without being treated as wastes. WCO recognize as a raw material for biodiesel process and have a great potential. Biodiesel is made through a reaction between triglyceride and alcohol, with triglyceride being a raw material found primarily in plants and animals. Transesterification is the popular process of biodiesel production with low cost and mild reactions conditions. Some studies have done on the variable of transesterification process with the optimum condition of biodiesel production from WCO. This study examines WCO as a raw material for biodiesel production, including the various variables of transesterification process and a comparison of WCO biodiesel and petroleum diesel.